2009
DOI: 10.1117/12.836901
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the predictive power of a calibrated physical stochastic resist model

Abstract: A newly developed stochastic resist model, implemented in a prototype version of the PROLITH lithography simulation software is fitted to experimental data for a commercially available immersion ArF photoresist, EPIC 2013 (Dow Electronic Materials). Calibration is performed only considering the mean CD value through focus and dose for three line/space features of varying pitch (dense, semi-dense and isolated).An unweighted Root Mean Squared Error (RMSE) of approximately 2.0 nm is observed when the calibrated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The first feature of interest was a 50nm line in a 100nm pitch imaged at 36.0 mJcm -2 and 0.05μm ('Best' focus). It should be noted that the standard deviation of the distribution for both experimental and simulation data is around 50% lower than that reported in the previous study [2]. This stems from a change in the way mean CD was determined for each sample.…”
Section: Stochastic Resist Model Predictionsmentioning
confidence: 45%
See 3 more Smart Citations
“…The first feature of interest was a 50nm line in a 100nm pitch imaged at 36.0 mJcm -2 and 0.05μm ('Best' focus). It should be noted that the standard deviation of the distribution for both experimental and simulation data is around 50% lower than that reported in the previous study [2]. This stems from a change in the way mean CD was determined for each sample.…”
Section: Stochastic Resist Model Predictionsmentioning
confidence: 45%
“…In previous studies [2,3] it has been shown that repeated runs of the stochastic resist model under identical process settings yield slightly different resist profile results. Since these variations are related to probabilistic statistics, repeated runs can be used to synthetic CDU distributions.…”
Section: Stochastic Resist Model Predictionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Different imaging characteristics are observed due to the varying pitch-to-CD ratio values. Dense and isolated line/space patterns are frequently used for resist modeling 27 , 28 , 30 32 and calibration 33 38 due to the significant differences in imaging characteristics between them. Consequently, the EXP-method 1 selects the patterns with the smallest and largest pitch-to-CD ratios as the critical patterns.…”
Section: Selection Results Of Critical Patterns Based On Different Me...mentioning
confidence: 99%